2008
DOI: 10.1073/pnas.0712280105
|View full text |Cite
|
Sign up to set email alerts
|

Acid-sensing ion channels interact with and inhibit BK K + channels

Abstract: Acid-sensing ion channels (ASICs) are neuronal non-voltage-gated cation channels that are activated when extracellular pH falls. They contribute to sensory function and nociception in the peripheral nervous system, and in the brain they contribute to synaptic plasticity and fear responses. Some of the physiologic consequences of disrupting ASIC genes in mice suggested that ASIC channels might modulate neuronal function by mechanisms in addition to their H ؉ -evoked opening. Within ASIC channel's large extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 47 publications
1
36
2
1
Order By: Relevance
“…2007). In contrast, in vitro studies have shown that BK channels reciprocally interact with ASICs via the toxin-like extracellular motif of ASICs (Petroff et al 2008). In contrast to these findings, we did not observe interactions between BK channels and ASICs in MHb neurones, suggesting that the mechanisms governing interactions between these ion channels are precisely regulated and might require concentrations achieved only in certain cell types.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…2007). In contrast, in vitro studies have shown that BK channels reciprocally interact with ASICs via the toxin-like extracellular motif of ASICs (Petroff et al 2008). In contrast to these findings, we did not observe interactions between BK channels and ASICs in MHb neurones, suggesting that the mechanisms governing interactions between these ion channels are precisely regulated and might require concentrations achieved only in certain cell types.…”
Section: Discussioncontrasting
confidence: 56%
“…The second conclusion that can be drawn from these studies is that, in spite of the high levels of nAChRs, BK channels and ASICs expressed in MHb neurones, and the reported interactions between these channels (Kong et al 2007;Petroff et al 2008;Zorrilla de San Martin et al 2010), nicotine-and acid-evoked currents in the MHb are insensitive to selective antagonists of BK channels and ASIC1a. Nicotinic acetylcholine receptors have been shown to be modulated by BK channels through the function of VGCCs in vestibular hair cells (Kong J Physiol 589.21 Figure 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASIC3 expression and activity are enhanced by several proinflammatory mediators, including bradykinin, serotonin, nerve growth factor, and glial cell linederived neurotrophic factor, that sensitize nociceptors (Voilley et al, 2001). At the central level, ASIC1a is the major component of ASICs and is required for acid-evoked currents in central neurons, where it contributes to neuronal excitability, synaptic plasticity, and dendritic spine development (Wemmie et al, 2002(Wemmie et al, , 2004Zha et al, 2006;Petroff et al, 2008). In the SDH, elevated ASIC1a activity has been shown to play a role in central sensitization and pain hypersensitivity (Duan et al, 2007;Mazzuca et al, 2007;Xu and Duan, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no evidence that ENaC channels are linked/coupled/interact with K ϩ channels, there is evidence that the closely related ASIC channels directly regulate certain K ϩ channels. 9 Thus, a heteromeric ENaC/ASIC channel could potentially regulate a K ϩ channel. Alternatively, ENaC proteins may interact with other ASIC proteins or putative endothelial mechanosensitive proteins (caveolin, integrins, etc) to form a multimeric flow-sensitive receptor complex that has altered amiloride sensitivity and more selectivity for K ϩ than Na ϩ .…”
Section: How Might Enac Mediatementioning
confidence: 99%